The harder we run : Black workers since the Civil War - Harris, William Hamilton, 1944- (New York : Oxford University Press, 1982)
Written clearly and passionately, employing both anecdotes and statistics, this comprehensive narrative traces the position of blacks in the American economy from the Civil War to the present. - From publisher description. Also includes sections on the legacy of slavery, northward migration, the brotherhood of Sleeping Car Porters, black workers during the depression and war
Koleksi Sumbangan : Dr. Syed Husin Ali.
Includes bibliographical references (pages 227-240) and index.
Keywords: African Americans -- Employment -- History